KONSEPSI IDEAL DARUSSALAM DALAM PERSPEKTIF A. HASJMY SEBAGAI PUSAT PENDIDIKAN ISLAM - Rahmad Syah Putra; Reza Hendra Putra; Amirul Haq RD (Universitas Islam Negeri Ar-Raniry Banda Aceh, 2020)
Darussalam is one of the names of the Student City Center (Kopelma) in Aceh. The city builder was designed by educational figures at that time as a post-war ideal in order to create a peaceful and peaceful Aceh atmosphere through educational and intellectual development. A. Hasjmy is one of the educational figures who did not have a central role in creating the initial foundation for the conception of Darussalam. This research is a qualitative research, and examines the ideal concept of Kopelma Darussalam as an education center. This research is expected to obtain an overview of how the ideal concept of Darussalam as a center for Islamic education in A. Hasjmy's view, with the data techniques used are interviews and documentation studies. Data analysis using steps of data reduction, data display, and withdrawal. Based on the results of this research, it can be implemented that A. Hasjmy has determined 4 main conceptions of Darussalam's ideal, including 1) Darussalam as a Model Campus; 2) Darussalam as a Symbol of Peace; 3) Darussalam is a Character Building; and 4) Darussalam as a Science Campus. Through the fourth concept, it is hoped that Darussalam will become a center of study and reference and be able to solve all problems in Aceh, as well as a place for developing knowledge to contribute to mankind, and be able to contribute to realizing the development of a dignified Aceh.